A Roadmap for Fighting Election Interference. (22nd January 2021) - Ohlin, Jens David
Abstract : If we have learned anything since the 2016 election, it is that foreign election interference is not just a strategic tool used by Russia. Many countries are now using social media disinformation as statecraft to attack democracies. With a relatively small investment of personnel and financial resources, a foreign power can use social media and other online tools to heighten divisions in the electorate, spread disinformation and conspiracy theories, and undermine confidence in the electoral system specifically and democratic institutions generally. The Biden administration should use the moral, political, and legal authorities of the Executive Branch to protect the United States from foreign election interference. In parallel, it should work cooperatively with allies to combat election interference using multilateral initiatives.